2021
DOI: 10.2337/dci21-0034
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Report: Definition and Interpretation of Remission in Type 2 Diabetes

Abstract: A consensus report of a particular topic contains a comprehensive examination and is authored by an expert panel (i.e., consensus panel) and represents the panel's collective analysis, evaluation, and opinion. The need for a consensus report arises when clinicians, scientists, regulators, and/ CONSENSUS REPORTDiabetes Care 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
152
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(164 citation statements)
references
References 38 publications
1
152
1
10
Order By: Relevance
“…Moreover, HbA1c alone is not always appropriate to diagnose diabetes, and, similarly, may not always be appropriate to diagnose remission, for example, for people with certain haemoglobinopathies or anaemia of chronic disease [ 8 , 29 ]. Other potential options include use of estimated HbA1c; however, this is not established in routine clinical settings [ 7 , 30 ]. This highlights the need for a definitive and comprehensive consensus on the definition of type 2 diabetes remission that is clear for people with type 2 diabetes and healthcare professionals in all settings [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, HbA1c alone is not always appropriate to diagnose diabetes, and, similarly, may not always be appropriate to diagnose remission, for example, for people with certain haemoglobinopathies or anaemia of chronic disease [ 8 , 29 ]. Other potential options include use of estimated HbA1c; however, this is not established in routine clinical settings [ 7 , 30 ]. This highlights the need for a definitive and comprehensive consensus on the definition of type 2 diabetes remission that is clear for people with type 2 diabetes and healthcare professionals in all settings [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IDF states that “remission is defined by most guidelines as an HbA1c below 6% (42 mmol/mol) without medication for 6 months or more” [ 5 ] (p. 21).” Buse and colleagues define remission as “achieving glycaemia below the diabetic range in the absence of active pharmacologic or surgical therapy.” Three types of remission are explicitly defined: partial remission, complete remission, and prolonged remission (cure) with a minimum duration of 1 year for partial and complete remission [ 6 ] (p. 2134). Riddle and colleagues define remission as “HbA1c <6.5% (48 mmol/mol) measured at least 3 months after cessation of glucose-lowering pharmacotherapy” (p. 1) [ 7 ] (at least 6 months after starting a lifestyle intervention) [ 7 ]. We have previously shown that there were at least 96 unique definitions of diabetes remission used in the research literature from 2009 to 2020 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…By summer of 2020, she reported that her pain and headaches had improved, with an overall improvement in quality of life, as she was able to move around and exercise without pain or discomfort. In July of 2021, her fasting blood glucose was measured at 108 mg/dL and HbA1c was at 5.4%: she is no longer on any diabetes medications and meets the definition of diabetes remission [63].…”
Section: Case 2 321 Overview Of Conditionmentioning
confidence: 99%
“…Moreover, HbA1c alone is not always appropriate to diagnose diabetes, and, similarly, may not always be appropriate to diagnose remission, for example, for people with certain haemoglobinopathies or anaemia of chronic disease [8,29]. Other potential options include use of estimated HbA1c; however, this is not established in routine clinical settings [7,30]. This highlights the need for a definitive and comprehensive consensus on the definition of type 2 diabetes remission that is clear for people…”
Section: Plos Medicinementioning
confidence: 99%